PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN MEMECAHKAN MASALAH DAN HASIL BELAJAR KOGNITIF BIOLOGI SISWA KELAS VII SMP NEGERI 14 SURAKARTA TAHUN PELAJARAN 2011/2012 - Siswanto, Siswanto; Maridi, Maridi; Marjono, Marjono (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? This research aims to determine the effect of PBL learning model of problem-solving skills and cognitive learning outcomes biology class VII students of SMP Negeri 14 Surakarta. PBL model is a model of learning by forcing students to practical problems or as a foothold in learning, in other words, students learn through the problems. Given the problems the students are challenged to find / search for a solution of real world problems can be resolved as a group (in collaboration). The cooperation will enable students in learning to improve problem-solving skills and cognitive learning outcomes. This research is a Quasi Experimental research design using a pretest-postest Control Group. Population is all students in grade VII Junior High School 14 Surakarta with cluster random sampling technique using sampling. Aspects of data collection techniques and problem-solving skills using the cognitive learning outcomes tests are analyzed using statistical tests anacova. Keywords: Model of Problem Based Learning (PBL), Problem Solving Ability, Cognitive Sciences Learning Outcomes